Metodología para la estimación del potencial de biomasa en Cienfuegos con fines energéticos (2017)
This paper presents the methodology used to calculate the present and future potentials of the total waste by biomass source. Based on the information provided by the leading producing companies of the province of Cienfuegos, it was possible to determine the overall energy delivered, as well as the reduction (in tons) of the CO2 emissions to the atmosphere from the lifting of the biomass of sugarcane, coffee, rice, and sawdust. In the case of the bagasse, the total energy was 4.409E+ 08 MJ and reduced 137 652.9 t of CO2 ; for its part, the total energy derived from the cachaza was 7.093E + 08 MJ and decreased 221 423.9 t of CO2. For the case of waste of coffee and rice and the remnants generated by sawmills, these values were 4.808E + 05 MJ (150.08 t of CO2), 6.347E + 07 MJ (19 813,24 t of CO2) and 4.108E + 07 MJ (12 24.19 t of CO2), respectively.